STUDENTS’ READING COMPREHENSION ACHIEVEMENT IN NARRATIVE TEXT THROUGH TEAM PRACTICE TECHNIQUE - Sholihatul Hamidah Daulay (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study was conducted to find out the students’ reading comprehension achievement in narrative text through team practice technique. This research was applied by class room action research. The technique of analyzing data of this study was applied by using qualitative and quantitative data. The qualitative data were taken from interview, diary notes, observation sheet and documentation. The quantitative data were taken from the best. It indicated that the work technique can improve students’ comprehension achievement in narrative text through team practice technique. It’s strengthened by the result of observation showed that most of the students in teaching learning process were active and serious in joining the lesson. They were active in discussing and they had already been brave to propose question and give the solution to the problem. Keywords: Reading Comprehensive, Narrative Texts, Team Practice Technique